Alternative Organizational Survival: A Comparison of Two Worker-Recuperated Businesses in Buenos Aires, Argentina. (20th July 2021) - Sobering, Katherine; Lapegna, Pablo
Abstract: It is widely accepted that economic indicators like efficiency, productivity, and profitability are key to explaining why some businesses survive and others do not. Yet not all work organizations ascribe to capitalist assumptions about ownership, authority, and even what constitutes success itself. Worker-recuperated businesses (WRBs) in Argentina—organizations closed by their private owners, occupied by their workers, and restarted as worker cooperatives—offer one such example. While research has documented the operational and financial challenges these businesses confront, we know little about why some survive and others do not. This article draws on qualitative and historical research in two WRBs in Buenos Aires: one that survived (Hotel Bauen) and one that closed (FORJA San Martín). Comparing the organizations' trajectories, we argue that labor process, geographic location, and political networks are key to understanding their survival. We find that different types of labor in industrial and service workplaces in conjunction with their geographic locations impacted efforts to develop networks with political actors, consumers, and social movements that provided legitimacy and resources to enable their continuity over time. The article discusses the contributions of these findings to theories of organizations and the implications for studying alternative work organizations.